2021
DOI: 10.21037/tau-21-730
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity extracorporeal shockwave therapy for erectile dysfunction: an overview of systematic reviews

Abstract: Background: Low-intensity extracorporeal shockwave therapy (LI-ESWT) may be a successful complementary treatment approach for erectile dysfunction (ED). In this study, we aimed to review and summarize the research evidence from systematic reviews (SRs)/meta-analyses (MAs) regarding the clinical effectiveness of LI-ESWT for ED.Methods: Studies on LI-ESWT for ED were searched using eight electronic databases from establishment of each database to 31 June 2021 with the language restrictions of Chinese and English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…LI‐SWT for ED has yet to be approved and applied as standard therapy protocol, as its efficacy is still incompletely defined, leading to some criticism among some experts in the field (Lei et al, 2021; Sokolakis & Hatzichristodoulou, 2019). However, some studies have stated that shock wave therapy for ED is an effective treatment option (Akande et al, 2021; Angulo et al, 2017; Caretta et al, 2021; Clavijo et al, 2017; Lu et al, 2017; Saltzman et al, 2022; Wang et al, 2020; Yao et al, 2022; Yuan et al, 2021). Scientific disagreement of the benefits of shock wave therapy may prompt patients to resort partially or completely to online sources to gain knowledge about LI‐SWT and aid in treatment decision making (Stukus, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…LI‐SWT for ED has yet to be approved and applied as standard therapy protocol, as its efficacy is still incompletely defined, leading to some criticism among some experts in the field (Lei et al, 2021; Sokolakis & Hatzichristodoulou, 2019). However, some studies have stated that shock wave therapy for ED is an effective treatment option (Akande et al, 2021; Angulo et al, 2017; Caretta et al, 2021; Clavijo et al, 2017; Lu et al, 2017; Saltzman et al, 2022; Wang et al, 2020; Yao et al, 2022; Yuan et al, 2021). Scientific disagreement of the benefits of shock wave therapy may prompt patients to resort partially or completely to online sources to gain knowledge about LI‐SWT and aid in treatment decision making (Stukus, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there was only one overview of SRs on ESWT [67]. Yuan et al used the AMSTAR 2, the Risk of Bias in Systematic Reviews (ROBIS), PRISMA, and GRADE to review 8 SRs on low-intensity ESWT for erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In an over view of eight systematic reviews, Yuan et al stated that Li-ESWT increased the participants' subjective scores mainly the IIEF-EF domain, also the objective EHS and penile hemodynamics were improved in the terms of PSV (11). Similarly, Yao et al analyzed 16 RCTs and reported that both IIEF and EHS in ED patients has increased after Li-ESWT treatment, notably in the moderate ED group.…”
Section: Discussionmentioning
confidence: 99%